THE EVALUATION OF THE STRUCTURAL FEATURES IMPACT OF THE LOCOMOTIVE TRACTION DRIVE ON THE STRESS STATE OF ITS ELEMENTS - Bondarev, O. M. (Science and Transport Progress, 2009)
In the article the research results on determination of levels of loading and stresses in the tractive drive elements, which can appear in operation conditions, under different variants of the tractive gear. On the basis of calculations executed the recommendations re. parameters of tractive gear elements, when their strength is provided, are put forward.